EFFECTIVENESS OF GROUP GUIDANCE SERVICES TO IMPROVE SELF ESTEEM OF GRADE VIII STUDENTS IN SMP NEGERI 7 BUKITTINGGI - Vekta Juliatrik; Hidayani Syam (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The background of the study is the phenomenon that occurs in students at SMP Negeri 7 Bukittinggi, there are still some students who tend to underestimate their talents and abilities, so that this lack of self-confidence can be seen from their reluctance to try new things and being less active in class discussions. There are still students who show a sense of helplessness when facing learning difficulties or personal problems. They often feel hopeless and lack initiative to find solutions, which has an impact on low academic achievement. Some students easily follow the negative behavior of friends, such as skipping school or using bad language, without considering the consequences. There are still students who tend to avoid situations that cause anxiety, such as speaking in front of the class or taking exams, which hinders their active participation in learning. This type of research is Pre-Experimental Design using the One Group Pretest-Posttest model. The population in this study was class VIII.3. The sample of this study was 10 people who were taken using the purposive sampling technique, which means the technique of determining the sample using certain considerations. Data was collected using the esteem cell scale. The data analysis technique used was the Wilcoxon test. The results of this study indicate that: (1) the description of students' self-esteem before being given group guidance services is in the low category with a mean of 18.00. (2) the description of students' self-esteem after being given group guidance services is in the medium category with an increasing score with a mean of 23.50. (3) group guidance services are effective in increasing students' self-esteem, this statement is supported by the results of the asymp sig (2-tailed) obtained a value of 0.005 which means it is smaller than the α value of 0.05. So it can be said that Ha is accepted and Ho is rejected, meaning that group guidance is effective in improving interpersonal communication of class VIII students at SMP Negeri 7 Bukittinggi.